(untitled) (Research, Society and Development, 2021)
Taking into account the existing problems in orthodontic traction procedures for impacted teeth regarding the fixation and maintenance of orthodontic pieces to the dental element, in view of the peculiarities of the oral environment, considering this, the present study aims to evaluate, through the review of the literature, bonding of orthodontic devices using Transbond™ Plus Color Change 3M hydrophilic adhesive and cyanoacrylate-based adhesives. In the present work, the literature review method was used with the theme Adhesion of orthodontic devices using hydrophilic adhesive Transbond™ Plus Color Change 3M and adhesives based on cyanoacrylate. Consequently, a search was performed in the databases MEDLINE, Portal BVS, Scielo and LILACS, between the years of 2012 and 2021, in Portuguese, English or Spanish. Right after applying the inclusion and exclusion criteria, twelve articles were selected. Given the above, it can be concluded that the bond strength of orthodontic devices using hydrophilic adhesive Transbond™ Plus Color Change 3M and cyanoacrylate-based adhesives varied in the studies, which can be explained by the methodological differences observed in these studies.